Mathematical Model of the Central Lombok Regency People’s Interest towards the COVID-19 Vaccination - Himmah, Elok Faiqotul; Riana, Riana (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
The COVID-19 vaccination program as an effort to prevent COVID-19 infection is still less attractive to the public in some areas in Indonesia, one of which is Central Lombok Regency. This is indicated by data on the number of complete vaccine recipients who still have not reached the threshold value for the formation of herd immunity. The factors that influence people's interest in COVID-19 vaccination can be analyzed using a mathematical model. This study aims to obtain a mathematical model of the interest of the people of Central Lombok Regency towards COVID-19 vaccination and to find out what factors most influence the interest of the people of Central Lombok Regency towards COVID-19 vaccination. The method used in this research is quantitative descriptive method. The data collection technique used a questionnaire that was given randomly to 332 respondents, namely the people of Central Lombok Regency in the age range of 12 to 70 years. Data analysis was based on multiple linear regression analysis with classical assumption tests, namely normality, multicollinearity, and heteroscedasticity tests. The results of the study obtained a mathematical model of the interest of the people of Central Lombok Regency towards COVID-19 vaccination. Variable of trust in the vaccine effectiveness and trust in the government are the factors that influenced the interest of the people of Central Lombok Regency towards COVID-19 vaccination.